Staged treatments of multiple pseudoaneurysms after total arch replacement. Issue 2 (25th November 2019) - Kitada, Yuichiro; Okamura, Homare; Arakawa, Mamoru; Miyagawa, Atsushi; Adachi, Hideo
Abstract: Background: An aortic pseudoaneurysm after cardiovascular surgery can be fatal. Methods/Results: Here, we describe the staged successful treatments of three pseudoaneurysms in a 77‐year‐old female patient who underwent total arch replacement and coronary artery bypass grafting 5 years ago. Computed tomography revealed three pseudoaneurysms: in the distal anastomosis of the total arch replacement, in the anastomosis of the left common carotid artery, and in the proximal anastomosis of the saphenous vein graft. Endovascular treatment and surgical repair were performed to treat these three pseudoaneurysms. Discussion: An aortic pseudoaneurysm is a rare complication after cardiac or aortic surgery. Here, we present a case of combined endovascular and surgical repairs of three pseudoaneurysms in one patient.